Respuesta :

Given the system of equations:

[tex]y=x-1 \\ y=-2x+5[/tex]

We solve the system as follows:

Step 1: Since both equations are in terms of y, we equate both equations to get:

[tex]x-1=-2x+5[/tex]

Next, we collect like terms, and solve for x, to get:

[tex]x+2x=5+1 \\ \\ 3x=6 \\ \\ x= \frac{6}{3} =2[/tex]

Next, we substitute for x into any of the previous eguations, substituting for x into the first equation, we get:

[tex]y=2-1=1[/tex]

Therefore, the solution to the system of equations is (2, 1)